Comparative Analysis Of Implementation Methods Soldier Pile And Sheet Pile Retaining Wall On The Construction Of Gwt Pt. Ubs Surabaya - Muhammad Alfian Eko Buwono; Koespiadi; Julistyana Tistogondo (Journal of World Conference (JWC), 2021)
Generally, a basement construction requires an appropriate Earth Retaining Wall to support the development process in the area. In the project area of ??PT. UBS Surabaya has the construction of a Soldier Pile which is arranged from Bored Pile and Bentonite Pile, the construction applies the Bottom Up and Dewatering method which means that construction starts from the subgrade level firstly and then the construction work goes up. This research was aimed to examine the existing types of retaining wall (Soldier Pile) with an alternative comparison of Corrugated Concrete Sheet Pile (CCSP). This is aimed to finding the effectiveness retaining wall that has been used with another methods so that it can affect to management in terms of cost and time which has been taken. Based on the comparison result of two methods, it is found that the use of the Soldier Pile method has a cost difference of Rp. 139,533,000,- less than the Sheet Pile method. However, the implementation time of the Sheet Pile method is 28 days faster than the Soldier Pile method, with this comparison, the Sheet Pile method is considered more effectively applied with an implementation time effectiveness ratio of 36.36% considering that the development project area is close to densely populated settlements. Based on the results of the comparison of the two methods, it is found that the use of the Soldier Pile method has a cost difference of Rp. 139,533,000,- less than the Sheet Pile method. However, the implementation time of the Sheet Pile method is 28 days faster than the Soldier Pile method, with this comparison, the Sheet Pile method is considered more effectively applied with an implementation time effectiveness ratio of 36.36% considering that the development project area is close to densely populated settlements.